CAR-T cell therapy in relapsed or refractory multiple myeloma and access in Turkey - Hakan, Goker; Engin, Kelkitli; Elifcan, Karakulak Aladag; Haluk, Demiroglu; Mehmet, Turgut; Suman, Kambhampati; Maxwell, Krem (Frontiers in Medicine, 2024)
The past decade has seen the development of immunotherapy for the treatment of multiple myeloma (MM), beginning with monoclonal antibodies (mAbs) in the relapsed and refractory setting and culminating in the market approval of chimeric antigen receptor T cells (CAR-T) and bispecific antibodies (BsAbs). The medical community is evaluating the efficacy and safety of these targeted immunotherapies, most of which currently target B-cell maturation antigen (BCMA) on the surface of plasma cells. Two anti-BCMA CAR-T products are available for treating relapsed or refractory MM: idecabtagene vicleucel (ide-cel) and ciltacabtagene autoleucel (cilta-cel). Ide-cel and cilta-cel demonstrate the ability to induce deep responses in heavily pretreated diseases, including patients with triple-class-refractory and penta-refractory diseases. However, there are key similarities and differences regarding these agents, unknowns regarding their comparative efficacy and toxicity, and mechanisms underlying resistance to these new immunotherapies. This review discusses CAR-T cell therapy in relapsed refractory MM, with a focus on efficacy, toxicities, and the evolving trajectories of these therapies in the USA, as well as access in Turkey.